Effects of work demands on physical therapists in the KSA. Issue 1 (February 2016) - Muaidi, Qassim I.; Shanb, Alsayed A.
الملخص: أهداف البحث: كثيراً مايرتبط الضغط الوظيفي بضعف المخرجات. نتيجة لطبيعة مهنتهم فقد سجل ممارسي العلاج الطبيعي مستويات مرتفعة من الضغط الوظيفي والاضطرابات في الجهاز العضلي الهيكلي. أُجريت هذه الدراسة لمعرفة مدى تأثير الضغوط البدنية والنفسية على ممارسي مهنة العلاج الطبيعي العاملين في المملكة العربية السعودية. طرق البحث: وُزعت استبانة محققة على ٨٥٠ معالجا طبيعيا لتقييم متطلبات العمل البدنية والنفسية، التي قد تؤدي إلى اضطرابات في الجهاز العضلي الهيكلي. تم تحليل البيانات إحصائيا باستخدام برنامج الحزمة الإحصائية للعلوم الاجتماعية. النتائج: سُجلت نسبة استجابة ٦٤٬٧٪ (٥٤٬٠٪ ذكور و٤٦٬٠٪ إناث). كانت الخبرة السريرية لغالبية المشاركين ١٢.٥ ± ٦.٥ سنة. وكانت القيم المتوسطة لمتطلبات العمل البدنية والنفسية ٣٧٬٨ ± ٨٬١ و١٨٬٦ ± ٥٬١ على التوالي. كما كان هناك ارتباطات ذوات قِيَم إحصائية بين كل من المتطلبات البدنية وإعدادات العمل، ومؤشر كتلة الجسم، وجنس المعالِج الطبيعي (٠٬٠٥ < p). وكانت القيم المتوسطة لكل من القدرة على اتخاذ القرار وتقدير المهارة والمساندة بين العاملين ودعم المشرف ٣٦٬٠١ ± ٣٬٦ و ٢١٬٢ ± ٢٬٣ و ٢٤٬٣ ± ٢٬٥ و٢٤٬٦ ± ٢٬٠ على التوالي. الاستنتاجات: أحس المعالِجون الطبيعيون في هذه الدراسة بأن بيئة عملهم إيجابية جدا. لديهم متطلبات عمل بدنية ونفسية متوسطة ودرجات من التحكم الوظيفي من متوسطة إلى عالية. قد يحتاجون إلى درجات قصوى من التحكم للقيام بوظائفهم بشكل تام ومُرضي. كما أبرزت هذه الدراسة الحاجة إلى إضافة تدابير سلامة واستراتيجيات خاصة لمنع أو التقليل من متطلبات العمل الزائدة المصاحبة ولتحسين جودة العناية بالمرضى. Abstract: Objectives: Job stress has been associated with poor outcomes. Physical therapists have reported high levels of job stress and musculoskeletal disorders as a result of the nature of their profession. This study was conducted to evaluate the effects of physical and psychological stress on physical therapists working in the KSA. Methods: A validated questionnaire was distributed to 850 physical therapists for the assessment of physical and psychological work demands that could possibly lead to musculoskeletal disorders. The data were statistically analysed using the SPSS statistical package. Results: A response rate of 64.7% (54.0% males and 46.0% females) was recorded. The clinical experience of the majority of participants was 12.5 ± 6.5 years. The mean values of physical and psychological work demands were 37.8 ± 8.1 and 18.6 ± 5.1, respectively. There were significant correlations between physical demands, work setting, BMI and gender ( p < 0.05). The mean values for decision authority, skill discretion, co-worker support and supervisor support were 36.01 ± 3.6, 21.2 ± 2.3, 24.3 ± 2.5, and 24.6 ± 2.0, respectively. Conclusions: Physical therapists have moderate physical and psychological work demands and moderate to high levels of job control. They think that their work situations are very positive and they may require exerting maximal levels of control to perform their jobs properly and adequately. Therefore health organizations should save the different strategies, facilities and ergonomic measures for physical therapists to avoid or minimize excessive stresses and work demands.